PERENCANAAN DAN PENGEMBANGAN EKOWISATA DIPULAU LINGKA PROVINSI KEPULAUAN RIAU - Widi Hardini; Baktivillo Sianipar (JURNAL MATA PARIWISATA, 2022)
Developing Lingka Island, Kepri Islands Province as an ecotourism destination in order that to promote the potentiality the Malay hidden cultural heritage event, the difficulties of changing nomadic to permanent life and in the way of surviving and that there has been a lot of artsy life to be seen and exposed such as a sea life environment, communities daily activities, enjoyable swimming, fishing in the free ocean, however the lack of stakeholders involvement nevertheless the only certain church institution struggled in keeping on this beauty magnificent pursuance to reach the sustainable ecotourism development through some proper or concrete strategies and the proper planning has to be developed as well.